Development of an AHP Model for Evaluating WiFi Quality based on Multicriteria - Hartono, David; Fibriani (SCOPUS ID=57192643331), Charitas (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Wi-Fi service quality not only supports academic and administrative activities, but also significantly impacts user productivity and satisfaction. The criteria examined in this study regarding Wi-Fi services include ease of access, network stability, connection speed, coverage, and security. This research is based on questionnaire data collected from 100 Wi-Fi users at the Faculty of Information Technology, Satya Wacana Christian University (FTI UKSW), which was used to determine the relative importance of each criterion. The main objective of this study is to determine the weight of each Wi-Fi service criterion using the Analytic Hierarchy Process (AHP) method. Based on the AHP analysis, the criterion with the highest priority is ease of access, with a weight of 0.417087. The weights for the other criteria are as follows: network stability at 0.259637, connection speed at 0.165161, coverage at 0.104853, and security at 0.053262, making security the lowest-priority criterion. From these findings, it can be concluded that ease of access to Wi-Fi has a significant influence on user satisfaction. This insight can serve as a recommendation for the university to improve its services—for instance, by adding more access points or implementing a single sign-on system for Wi-Fi access.